Dampak Beban Kerja dan Stress Terhadap Niat Pergantian Karyawan di PT.MYS Bakti Cibitung - Lintang Walarian; Maulvi Nazir Ahmad Al Arif (Jurnal Publikasi Ilmu Manajemen, 2024)
At PT. MYS BAKTI CIBITUNG, a company that specializes in the transportation industry, the purpose of this study was to determine the degree to which workload and work stress directly affect inclusion turnover intentions. An approach to descriptive quantitative data analysis is used. There are 56 employees in the population under investigation in this study. Saturated sampling is the method of data collection employed, in which every member of the population is selected as a sample.. The data analysis results demonstrate that the workload hypothesis 1 is reasonable. The study's findings demonstrate a strong positive relationship between workload and the desire to switch jobs, which is supported by a t-statistic value of 7.866 that is higher than the figure of 1.96 and has a p-value of 0.0000. The second hypothesis, which demonstrated that work-related stress has a significant positive influence on employee turnover desires, was deemed acceptable. Based on a t-statistic value of 6,426 this conclusion has been drawn. surpassed the 1.96 threshold, with a p-value of 0.000.